Brain imaging and neuropsychiatric profiles associated with plasma cortisol level among nondemented older adults: Neuroimaging / Multi‐modal comparisons. (7th December 2020) - Oh, Hwamee; Leung, Hoi‐Chung; Canli, Turhan; Slifstein, Mark
Abstract: Background: A predisposition to stress or expression of chronic stress‐related symptoms has been considered as a risk factor for Alzheimer's disease (AD). To elucidate a neural mechanism underlying the risk of AD, we examined the relationship between glucocorticoids, glucose metabolism, hippocampal volume, and subsequent amyloid deposition among nondemented older adults. Method: We assessed plasma cortisol level (cortisol), FDG counts in AD signature cortical regions, adjusted hippocampal volume, cognitive and neuropsychiatric measures and subsequent amyloid accumulation in 58 cognitively normal older adults (CNs) and 396 participants with mild cognitive impairment (MCIs) in the Alzheimer's Disease Neuroimaging Initiative. Multiple regression models were applied to assess the relationships between these measures across all groups, followed by within‐group analyses. For psychological measures, neuropsychiatric inventory (NPI) scale total scores were assessed in relation with cortisol and neuroimaging measures. Result: Higher cortisol was associated with smaller adjusted hippocampal volume and greater NPI scores. With glucosemetabolic rates in AD signature regions, higher cortisol was associated with lower glucose metabolism in the MCI group, but with increased glucose metabolism in the CN group. Smaller hippocampal volume, but not higher cortisol, at baseline, was related to higher brain amyloid burden over time. Conclusion: Individuals' susceptibility to stress as measured by plasma cortisol levels may confer risk for neurodegeneration and the development of AD pathology among nondemented older adults.